Seeking the significance of music education : essays and reflections - Reimer, Bennett; MENC, the National Association for Music Education (U.S.) (Lanham, Md. : Rowman & Littlefield Education, 2009)
"Noted music educator Bennett Reimer has selected 24 of his previously published articles from a variety of professional journals spanning the past 50 years. During that time, he's tackled generating core values for the field of music education; the core in larger societal and educational contexts; what to teach and how to teach it effectively; how we need to educate our teachers; the role of research in our profession; and how to improve our future status."--Provided by publisher.
-- Our values as a school subject. Generating core values ; Core values in larger contexts -- Achieving our values. What and how to teach ; Educating our teachers ; The role of research -- Preserving and enhancing our viability. Our values in service of our future.
"Published in partnership with MENC, The National Association for Music Education."
Includes bibliographical references.
Includes bibliographical references.
Keywords: Music -- Instruction and study -- Philosophy